2021
DOI: 10.14416/j.asep.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cleaner Environment Approach by the Utilization of Low Calcium Wood Ash in Geopolymer Concrete

Abstract: The waste disposal issues were the most severe problems that could cause global warming, which depletes the environment. The research hypothesis was to find the suitability and sustainability of utilizing the waste by-products in the invention of green geopolymer concrete to eliminate the tremendous effects caused by the wastes. Due to the increased demand for fly ash in recent years, the requirement of high alkaline activators, and elevated temperature for curing, there was a research gap to find an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…The micro-filler effect of BMW is also responsible for the high CST of the mixes as it is suggested that the use of 30% BMW as replacement of GGBFS in GPC has resulted in high CST (Suresh Kumar et al 2022a , b , c , 2023 ; Arunachalam et al 2022 ). The enhanced CST is also reported, when the replacement of fly ash in GPC by 30% waste wood ash is done (Arunkumar et al 2023 , 2021 , 2022a , b ; Arun et al 2022 ). The use of waste glass powder along with BMW in GPC has resulted in compact bonding ultimately resulting in high CST (Suresh Kumar et al 2022b , c ).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The micro-filler effect of BMW is also responsible for the high CST of the mixes as it is suggested that the use of 30% BMW as replacement of GGBFS in GPC has resulted in high CST (Suresh Kumar et al 2022a , b , c , 2023 ; Arunachalam et al 2022 ). The enhanced CST is also reported, when the replacement of fly ash in GPC by 30% waste wood ash is done (Arunkumar et al 2023 , 2021 , 2022a , b ; Arun et al 2022 ). The use of waste glass powder along with BMW in GPC has resulted in compact bonding ultimately resulting in high CST (Suresh Kumar et al 2022b , c ).…”
Section: Resultsmentioning
confidence: 89%
“…The micro-filler effect of BMW is also responsible for the high workability of the mixes as it is suggested that the use of 30% BMW as replacement of GGBFS in GPC has resulted in high workability (Suresh Kumar et al 2022a , b , c , 2023 ; Arunachalam et al 2022 ). The enhanced workability is also seen when the replacement of fly ash in GPC by 30% waste wood ash is done (Arunkumar et al 2023 , 2021 , 2022a , b ; Arun et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020) mentioned that replacing by cement at 5, 10, 15, 20, 25 and 30% by wood ash had optimum strength values between 25% and 30%. Likewise, according to the research conducted by Arunkumar et al (2022a), the results of their study showed that replacing 30% of wood ash with fly ash resulted in better performance in all mechanical parameters of concrete, since from 40% to 100% substitution its strength progressively decreased below half of its standard strength at 28 days of rupture. However, the findings of Shaker et al (2020) support that wood ash can be used up to 25% in total weight of cement, the concrete does not lose its considerable strength in 28-day tests, as doses higher than 25% or even 50% reduced the strength to half of the 0% replacement in 28-day tests According to Bikoko (2021), he used eucalyptus wood ashes where they mention that they have a negative influence on the strength of concrete when replaced and added with respect to the weight of cement, respectively.…”
Section: Flexural Strengthmentioning
confidence: 98%
“…Plenty of research works focus on the utilization of flyash for the development of geopolymer concrete [6][7][8], bio medical waste ash [9,10], wood ash [11][12][13][14][15], GGBS [16][17][18]. Low calcium fly ash is widely preferred owing to its abundance availability and cheap cost.…”
Section: Introductionmentioning
confidence: 99%